Integrated mindfulness-based intervention: Effects on mindfulness skills, cognitive interference and performance satisfaction of young elite badminton players - Doron, J.; Rouault, Q.; Jubeau, M.; Bernier, M. (Psychology of Sport and Exercise, 2020)
Highlights: The 8-week Mindfulness Badminton Integrated (MBI) programme is presented. This study evaluated the MBI`s impact through a mixed methods approach. The MBI did not lead to clear improvement when compared to an active control group. Social validation provided additional insights into overall perceptions of the MBI. The findings have implications for researchers and practitioners.